Implementation Of Inclusive Education In Elementary School - Carissa Dwilanisusantya (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Inclusive education at the school level has obstacles that are often difficult to resolve. The local government appoints several schools in its area to accept children with special needs and are designated as inclusive schools. However, some of the designated schools do not meet the requirements to become inclusive schools. Schools accept children with special needs because of regulations that prohibit rejecting students with special needs. Based on the existing problems, it is very necessary to research to find out how to provide education for children with special needs in elementary schools who have not been able to meet the requirements to be designated as inclusive schools. This study used qualitative research methods. Based on the research results, it is known that inclusive education must be implemented by all public schools in Indonesia by accepting all types of special needs that children have. Most schools do not yet have a Special Guidance Teacher so they rely more on available teachers. Curriculum, methods, and assessments are also generally given the same as other students. In general, the implementation of inclusive education for children with special needs has not been in accordance with applicable regulations.